Pengaruh Model Pembelajaran Direct Instruction Terhadap Hasil Belajar Teknik Dasar Senam Lantai di SMAN 1 Klari - Islami Tefa, Muhamad Zidan Syahdilla; Abduloh, Abduloh; Kurniawan, Feby (Peneliti.net, 2023)
In the implementation of floor gymnastics learning activities in schools, student behaviors are often found that are not in accordance with expectations. Students feel afraid, hesitant and embarrassed to do the gymnastic movements taught by the teacher. The behavior of students who are afraid and hesitant when starting to do movements, students are afraid of being laughed at and made fun of when doing movements and have an impact on students losing their confidence, physical state. Lack of strength and flexibility is one of the inhibiting factors in gymnastics learning activities, the talents of students are very different, some learn quickly and some are slow. This type of research is experimental research. Experimental research is a study in which at least one variable is found that is manipulated to study cause-and-effect relationships. The research conducted was a pre-experimental study, with a research design in the form of